2017
DOI: 10.1007/s00204-017-1990-1
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker monitoring of controlled dietary acrylamide exposure indicates consistent human endogenous background

Abstract: The aim of the present study was to explore the relation of controlled dietary acrylamide (AA) intake with the excretion of AA-related urinary mercapturic acids (MA), N-acetyl-S-(carbamoylethyl)-l-cysteine (AAMA) and N-acetyl-S-(1-carbamoyl-2-hydroxyethyl)-l-cysteine (GAMA). Excretion kinetics of these short-term exposure biomarkers were monitored under strictly controlled conditions within a duplicate diet human intervention study. One study arm (group A, n = 6) ingested AA via coffee (0.15–0.17 µg/kg bw) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 10 publications
4
34
0
1
Order By: Relevance
“…As case in point, vegan-female-3 excreted within 72 h about 64% of the respective dietary AA intake (546 nmol) on day 2 as AAMA. Under strictly controlled conditions, a sustained endogenous background exposure to AA had compellingly been demonstrated in the above studies (Goempel et al 2017;Ruenz et al 2016). The present study also supports the premise of a steady background, as exemplified for vegan-female-3.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…As case in point, vegan-female-3 excreted within 72 h about 64% of the respective dietary AA intake (546 nmol) on day 2 as AAMA. Under strictly controlled conditions, a sustained endogenous background exposure to AA had compellingly been demonstrated in the above studies (Goempel et al 2017;Ruenz et al 2016). The present study also supports the premise of a steady background, as exemplified for vegan-female-3.…”
Section: Discussionsupporting
confidence: 87%
“…2b) showed excretion kinetics obviously undisturbed by smoke exposure, comparable to those also observed previously in human intervention studies under strictly controlled conditions. These have indicated that an AA intake of 1.3-1.8 µg/kg bw resulted in a mean of 58% of the ingested AA being excreted as AAMA (7% as GAMA) within 72 h. (Goempel et al 2017;Ruenz et al 2016) In the present study in free-living individuals, about similar excretion kinetics were seen. AAMA was excreted in less than 72 h with a maximum value already reached within 12 h after the reported dietary intake.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations